THE EFFECT OF GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLES ON EMPLOYEE PERFORMANCE AT BANK SYARIAH INDONESIA - Mufid, Fatiyah; Gusniarti, Gusniarti (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The purpose of this study is to determine the effects of various Good Corporate Governance principles on Bank Syariah Indonesia employees, specifically in the area of employee work performance and the effects of various Good Corporate Governance principles on employee work practices that are adapted from social theory. This study employs a quantitative approach with analysis description. Data was collected via a Likert scale questionnaire given to 100 respondents, using the Slovin survey, which is administered by Bank Syariah Indonesia employees. The results of this article's analysis show that the principles of good corporate governance have a simultaneous impact on employees' work at Bank Syariah Indonesia. Subsequently, the principles of accountability and responsibility have a significant impact on employee work. Conversely, the principles of transparancy, independence and fairness do not indicate significant effects on employees' work performance. This has important implications for Bank Syariah Indonesia management team in developing a plan to increase employee productivity, and management teams must pay more attention to the application of the Good Corporate Governance principles.